Experimental and molecular modelling approach for rapid adsorption of Bisphenol A using Zr and Fe based metalâorganic frameworks - Mahmad, A. (Elsevier B.V., 2022)
The synthesized highly porous functionalized metalâorganic frameworks (MOFs) are the solution for the rapid removal of toxic pollutants from wastewater. Bisphenol A (BPA) which consists of a derivative of phenol was identified as the primary pollutant in environmental waters and requires elimination for a sustainable and greener environment. In this work, we reported highly porous and stable Zr and Feâbased metalâorganic frameworks as adsorbents for the removal of BPA in an aqueous solution. In this study, MILâ88(Fe) (MIL stands for MatÃ©riaux de l'Institut Lavoisier) and UiOâ66(Zr) (UiO stands for University of Oslo) were synthesized by solvothermal techniques and characterized by fourier transformed infrared spectroscopy (FTIR), xâray diffraction (XRD), energyâdispersive xâray spectroscopy (EDX), field emission scanning electron microscopy (FESEM), scanning electron microscopy (SEM) and nitrogen adsorptionâdesorption measurements. MILâ88(Fe) and UiOâ66(Zr) had 1242 and 1421 mg2/g surface area, respectively. In the experimental study, the UiOâ66(Zr) and MILâ88(Fe) removed 99.25 and 98.36 BPA, respectively. Compared to MILâ88(Fe), UiOâ66(Zr) showed faster adsorption of BPA. The process was exothermic and spontaneous. The pseudoâsecond order model suited the kinetics studies well, while the Langmuir model fit the MILâ88(Fe) and UiOâ66(Zr) isotherms. Molecular docking was used to study the surface interactions of MILâ88(Fe) and UiOâ66(Zr) with BPA. The process involved van der Waals and hydrogen interactions between BPA with MILâ88(Fe) and UiOâ66(Zr) surfaces. Both MOFs proved to have high efficacy and appropriateness for the practical application of BPA adsorption from an aqueous solution. Â© 2022 Elsevier B.V.